MoS2 nanosheets covalently functionalized with polyacrylonitrile: synthesis and broadband laser protection performance. Issue 45 (13th November 2017) - Shi, Makai; Dong, Ningning; He, Nan; Wan, Yan; Cheng, Hongxia; Han, Mengru; Wang, Jun; Chen, Yu
Abstract : Highly soluble polyacrylonitrile (PAN)-covalently grafted MoS2 nanosheets (MoS2 –PAN) were synthesized in situ . This material shows superior optical limiting response in the visible and near-infrared ranges. Abstract : Highly soluble polyacrylonitrile (PAN)-covalently grafted MoS2 nanosheets (MoS2 –PAN) were synthesized in situ through reversible addition fragmentation chain transfer (RAFT) polymerization. In comparison with MoS2 and the MoS2 /PAN blends, whether in solution or in a PMMA matrix, the MoS2 –PAN-based samples show superior optical limiting response in the visible and near-infrared ranges. After annealing at 200 °C in N2 for 4 hours, the annealed MoS2 –PAN/PMMA film exhibits significantly enhanced nonlinear optical and optical limiting responses when compared to the non-annealed MoS2 –PAN/PMMA film. The observed nonlinear coefficients of the MoS2 –PAN/PMMA film are changed from 1015 cm GW −1 at 532 nm and 534 cm GW −1 at 1064 nm before annealing to 1151 cm GW −1 at 532 nm and 699 cm GW −1 at 1064 nm after annealing. The limiting thresholds were also decreased from 1.98 J cm −1 at 532 nm and 3.60 J cm −1 at 1064 nm before annealing to 1.56 J cm −1 at 532 nm and 2.67 J cm −1 at 1064 nm after annealing.